Analisis Faktor Pengaruh Keamanan Barang Selama Proses Transit pada Layanan Ekspedisi JNE di Purwakarta - Ardilah Tata Wijanarko; Risto Aditya; Muhammad Faisal Irgi Al Galih; Osep Hijuzaman (Widyatama University, 2026)
This study aims to analyze the effect of officer handling, delivery accuracy, tracking system, facility security, and delivery guarantee on the security of goods during the transit process on JNE expedition services in Purwakarta Regency. The method used is empirical quantitative with a positivistic paradigm, where a sample of 96 respondents was selected through a purposive sampling technique and the data was analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) through SmartPLS 4 software. The results of the analysis and discussion show an R-Square value of 0.503, indicating that the five independent variables simultaneously are able to explain 50.3% of the variation in goods security. Partially, only the delivery guarantee variable has a positive and significant effect (P = 0.012), while officer handling (P = 0.060), delivery accuracy (P = 0.649), tracking system (P = 0.170), and facility security (P = 0.409) do not have a significant effect. The research conclusion confirms the certainty of financial protection as the most important factor, so it is recommended that JNE Purwakarta management restructure resource priorities to simplify the insurance claim process and educate about the transparency of goods protection while maintaining warehouse operational standardization. The theoretical implications prove the separation of consumer perceptions that tracking technology and physical facilities are now only mandatory standards (must-have), while the practical implications show that legal and financial guarantees are the main triggers for customer security as well as driving the company's internal commitment to tighten operational controls.